Low and high surface brightness galaxies at void walls - Ceccarelli, Maria Laura (2012)
We study the relative fraction of low and high surface brightness galaxies (LSBGs and HSBGs)at void walls in the Sloan Digital Sky Survey (SDSS) Data Release 7.We focus on galaxies inequal local density environments. We assume that the host dark matter halo mass (for whichwe use SDSS group masses) is a good indicator of local density. This analysis allows us toexamine the behaviour of the abundance of LSBGs and HSBGs at a fixed local density anddistinguish the large-scale environment defined by the void geometry. We compare galaxiesin the field and in the void walls; the latter are defined as the volume of void shells of radiusequal to that of the void.We find a significant decrement, a factor of 4, of the relative fractionof blue, active star-forming LSBGs in equal-mass groups at the void walls and the field. Thisdecrement is consistent with an increase of the fraction of blue, active star-forming HSBGs.In contrast, red LSBGs and HSBGs show negligible changes. We argue that these results areconsistent with a scenario where LSBGs with blue colours and strong star formation activityat the void walls are fuelled by gas from the expanding void regions. This process could leadto LSBG to HSBG transformations.